Kídàn Dárán Sállá: Music for the Eve of the Muslim Festivals of '?D AL-FITR and '?D AL-KAB?R IN KANO, NIGERIA, by Fremont E. Besmer, published by the African Studies Program, Indiana University, 1974, pp. 84, $2.00. - Gourlay, Ken A. (International Library of African Music, 1980)
pages: 133-134
Keywords: Festivals; African Music; Nigeria; Muslim Festivals